2009
DOI: 10.1182/blood-2008-07-167056
|View full text |Cite
|
Sign up to set email alerts
|

Clonal analysis of deletions on chromosome 20q and JAK2-V617F in MPD suggests that del20q acts independently and is not one of the predisposing mutations for JAK2-V617F

Abstract: We developed a real-time copy number polymerase chain reaction assay for deletions on chromosome 20q (del20q), screened peripheral blood granulocytes from 664 patients with myeloproliferative disorders, and identified 19 patients with del20q (2.9%), of which 14 (74%) were also positive for JAK2-V617F. To examine the temporal relationship between the occurrence of del20q and JAK2-V617F, we performed colony assays in methylcellulose, picked individual burst-forming units-erythroid (BFU-E) and colonyforming units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 26 publications
(32 reference statements)
2
51
1
1
Order By: Relevance
“…25,26 In these cases, a BCR-ABL1-negative clone carrying JAK2 mutation appears during the course of imatinib treatment. In addition, clonal heterogeneity has been demonstrated in cases of myeloproliferative neoplasms with del(20q) 27 and myelodysplastic syndromes with isolated 5q deletion associated with JAK2 mutation. 28 TET2 mutations are the most common genetic abnormality found in chronic myelomonocytic leukemia, being present in around 40% cases.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 In these cases, a BCR-ABL1-negative clone carrying JAK2 mutation appears during the course of imatinib treatment. In addition, clonal heterogeneity has been demonstrated in cases of myeloproliferative neoplasms with del(20q) 27 and myelodysplastic syndromes with isolated 5q deletion associated with JAK2 mutation. 28 TET2 mutations are the most common genetic abnormality found in chronic myelomonocytic leukemia, being present in around 40% cases.…”
Section: Discussionmentioning
confidence: 99%
“…Last, as deregulation of HGF and/or IL-11, gp130 and STAT3 is common to many tumoral processes, the genetic events resulting in over-expression of these molecules in PV are unlikely to be primary events causing PV, but rather, frequent parallel events that occur independently of JAK2 mutation(s) and are also found in other malignancies, as described in MPN for several cytogenetic abnormalities (Kralovics, 2008;Schaub et al, 2009). Parallel or 'passenger' genetic events responsible for the deregulation of HGF and IL-11 would be consistent with the observations that not all PV patients show high levels of HGF, and that JAK2V617F alone does not ensure a PV phenotype nor the expansion of progenitors bearing this mutation.…”
Section: Cell Proliferationmentioning
confidence: 99%
“…Yet, in murine models, JAK2V617F is associated with polycythemia only when expressed at high levels (450% JAK2V617F-mutated alleles), whereas a significant proportion of PV patients carry o50% JAK2V617F (Lacout et al, 2006;Lippert et al, 2006;Wernig et al, 2006;Tiedt et al, 2008). We now know that the JAK2V617F mutation is frequently associated with other molecular genetic abnormalities and that the JAK2V617F mutation can occur several times in certain patients; moreover, the presence of JAK2V617F does not ensure expansion of mutated progenitors (Nussenzveig et al, 2007;Kralovics, 2008;Lambert et al, 2009;Schaub et al, 2009;Cleyrat et al, 2010). Hence, the role of JAK2V617F in MPN and the consequences of its expression in hematopoietic progenitors remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…PU.1 is necessary for the generation and function of macrophages and granulocytes through the regulation of essential myeloid genes such as the granulocyte/macrophage colony-stimulating factor receptor (GM-CSFR), the macrophage CSF (M-CSF), the granulocyte CSF (G-CSF), CD11b, myeloperoxidase, lysozyme, neutrophil elastase, CD45, and others. [1][2][3] Anti-apoptotic Bcl2 proteins are frequently overexpressed during tumorigenesis 4 and three of them are expressed in myeloid cells: BCL2A1 (also designated as A1 or BFL-1) and Mcl-1 in neutrophils, whereas BCL2A1 and Bcl-x L can both be upregulated in macrophages by proinflammatory stimuli in vitro. Sevilla et al 5 reported that PU.1 together with another Ets-family member, Ets2, transactivate the Bcl-x L promoter and increase macrophage survival.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Indeed healthy donors were reported positive for JAK2-V617F using nested PCR assays, and the repeated occurrence of the V617F mutation of JAK2 has been demonstrated in essential thrombocythemia (ET) and in PV. [3][4][5] In addition, in 2 PV patients, JAK2-V617F and mutations in exon 12 of JAK2 co-existed in separate sub-clones originating from a single progenitor in one case, or from unrelated hematopoietic stem cells in the other case. 6,7 V617F-positive PV patients with additional mutation(s) in exon 14 of JAK2 (V615L, C616Y, C618R and D620E) are also evidence of multiple JAK2 mutations.…”
mentioning
confidence: 99%